Impact of different formulations of platelet lysate on proliferative and immune profile of equine mesenchymal stromal cells - Yaneselli, Kevin; Ávila, Gimena; Rossi, Andrea; Rial, Analía; Castro, Sabrina; Estradé, María José; Suárez, Gonzalo; Algorta, Agustina (Frontiers in Veterinary Science, 2024)
Platelet lysate (PL) is investigated as a potential replacement for fetal bovine serum (FBS) in cell culture. However, there is limited research on its impact on the immune profile of equine mesenchymal stromal cells (eMSCs). This study aimed to evaluate the effects of different PL formulations on the proliferative capacity, multipotentiality, and immune profile of equine adipose tissue-derived MSCs (eAD-MSCs). In vitro growth kinetics and trilineage differentiation of eAD-MSCs (n = 7) were assessed under three culture conditions: medium-concentration PL (MPL), high-concentration PL (HPL), and FBS as a control. The immune profile was evaluated by studying the expression of immunogenic receptors such as MHC I, MHC II, and immunomodulatory molecules IL-6, IL-10, and TNF-α, determined by gene expression, surface marker expression, and cytokine quantification. Both PL formulations, pooled from 5 donors, exhibited 3.3 and 6.5-fold higher platelet counts than baseline plasma for MPL and HPL, respectively. Higher concentrations of TGF-β and PDGF were found in both PL formulations compared to baseline. Furthermore, MPL and HPL subcultures demonstrated proliferative, clonogenic, and multipotent capacities similar to FBS. The immune profile of PL-cultured cells exhibited gene expression levels related to immunogenicity and immunomodulation similar to the reference condition, and the surface antigen presence of MHC II was also similar. However, HPL media exhibited higher IL-6, IL-10, and TNF-α concentrations in the culture supernatant. In conclusion, both PL media contained higher concentrations of growth factors compared to FBS, supporting the in vitro culture of eAD-MSCs with proliferative, clonogenic, and multipotent capacity similar to the reference medium. Nonetheless, PL usage led to a variation in the immunomodulatory cytokine microenvironment, with higher concentrations of IL-6, IL-10, and TNF-α in HPL media compared to MPL and FBS.